Hydroxyapatite as Delivery and Carrier Material: Systematic Literature Review with Bibliometric Analysis - Noviyanti, Atiek Rostika; Adzkia, Qurratu Aini Alya; Novella, Indrika; Kurnia, Irwan; Suryana, S.; Ma'Amor, Azman Bin; Irwansyah, Ferli Septi (Universitas Pendidikan Indonesia (UPI), 2024)
Hydroxyapatite (HA), a bioactive calcium phosphate compound, has garnered significant attention in biomedical and pharmaceutical research due to its remarkable properties as a delivery and carrier material. This review aims to comprehensively analyze the extensive research surrounding HA's applications in drug delivery and as a carrier for various therapeutic agents, encompassing various studies from scientific articles focusing on HA-based systems designed for drug delivery, tissue engineering, and other therapeutic applications. The review also investigates the HA synthesis and modification methods for tailored drug release profiles, as well as the interaction between HA and bioactive molecules. Key findings from the review include the versatility of HA as a biocompatible carrier, its ability to facilitate controlled drug release, and its potential to enhance tissue regeneration. The review identifies trends in HA-based delivery systems, highlighting recent advances and emerging research directions, as well as providing valuable insights into the current state of HA-based drug delivery and carrier materials, shedding light on the potential of HA to revolutionize the field of biomedicine. It serves as a valuable resource for researchers, clinicians, and pharmaceutical professionals seeking to harness the capabilities of HA in developing innovative therapeutic strategies.